EARLY-ONSET FAHR SYNDROME IN SIBLINGS: NEURODEVELOPMENTAL DISSOCIATION BETWEEN COGNITIVE IMPAIRMENT AND BEHAVIORAL DYSREGULATION - Dymon, Marcelina; Wawrzonek, Katarzyna; Warzocha-Żurek, Daria Aleksandra; Andryszko, Krystian; Szwed, Agnieszka; Polewczak-Karp, Ewa Maria; Ziemba-Furgała, Natalia; Sołtys, Aleksandra; Borzęcka, Katarzyna Anna; Krysa, Paulina (International Journal of Innovative Technologies in Social Science, 2026)
Fahr syndrome (FS), also known as primary familial brain calcification (PFBC), is a rare and heterogeneous neurodegenerative disorder characterized by bilateral intracranial calcifications, most commonly affecting the basal nuclei. Although the condition is typically associated with movement disorders in adults, increasing attention has been given to early-onset cases, particularly in children, where the clinical presentation often differs from the classical phenotype.This study examines cognitive, emotional, and behavioral functioning in two siblings diagnosed with early-onset Fahr syndrome. By combining neurological assessment, developmental psychopathology, and neuropsychological evaluation, the analysis provides insight into variability observed within the same family.The results indicate marked differences between the siblings despite a shared genetic and environmental background. Notably, cognitive deficits did not consistently correspond with emotional or behavioral disturbances. This suggests that the extent of calcifications alone may not fully explain functional outcomes. Instead, factors such as the timing of neurodevelopmental disruption, environmental influences, and possible genetic modifiers may play an important role.These findings highlight the importance of early neuropsychological assessment and support a multidisciplinary approach to diagnosis and care. They also point to the possibility that the clinical spectrum may extend beyond classical PFBC, underlining the need for broader genetic and metabolic evaluation.